MAPKAP Kinase-2 Drives Expression of Angiogenic Factors by Tumor-Associated Macrophages in a Model of Inflammation-Induced Colon Cancer - Suarez-Lopez, Lucia; Kong, Yi Wen; Sriram, Ganapathy; Patterson, Jesse C.; Rosenberg, Samantha; Morandell, Sandra; Haigis, Kevin M.; Yaffe, Michael B. (Frontiers in Immunology, 2021)
Chronic inflammation increases the risk for colorectal cancer through a variety of mechanisms involving the tumor microenvironment. MAPK-activated protein kinase 2 (MK2), a major effector of the p38 MAPK stress and DNA damage response signaling pathway, and a critical regulator of pro-inflammatory cytokine production, has been identified as a key contributor to colon tumorigenesis under conditions of chronic inflammation. We have previously described how genetic inactivation of MK2 in an inflammatory model of colon cancer results in delayed tumor progression, reduced tumor angiogenesis, and impaired macrophage differentiation into a pro-tumorigenic M2-like state. The molecular mechanism responsible for the impaired angiogenesis and tumor progression, however, has remained contentious and poorly defined. Here, using RNA expression analysis, assays of angiogenesis factors, genetic models, in vivo macrophage depletion and reconstitution of macrophage MK2 function using adoptive cell transfer, we demonstrate that MK2 activity within macrophages is both necessary and sufficient for tumor angiogenesis during inflammation-induced cancer progression. We identify a critical and previously unappreciated role for MK2-dependent regulation of the well-known pro-angiogenesis factor CXCL-12/SDF-1 secreted by tumor associated-macrophages, in addition to MK2-dependent regulation of Serpin-E1/PAI-1 by several cell types within the tumor microenvironment.